Inmediate Implant Placement in Maxillary Molars Using Septa Dilatation with Threaded Expanders - Luchetti, César Gabriel (2009)
Immediate placement of dental implants has shown to reduce treatment times and a better preservation of the alveolar ridge. This concept has limitations during replacement of tooth with 2 o 3 roots. The upper molar region also presents a lower bone density and the presence of the maxillary sinus. In the latest times, many attempts have been made to place implants in extraction sockets in this area, while some still think that the best option is the delayed approach. Immediate options include placement of the implant in the palatal socket off axis or modification of the palatal socket, among others. In a previous work, we presented a technique to place immediate implants in upper molars area, using the interseptal bone, which has shown better results compared to the delayed approach after the bone healing8. The original technique included the use of sharpened end osteotomes and a partial thickness rotated palatal flap to achieve primary closure. As an evolution of the technique, two years ago we started to make the dilatation using threaded expanders, in order to try a more comfortable procedure for the patient. This includes the use of a healing abutment to place the implant on a one stage basis. The aim of this study was to improve a proved technique and to compare it to the original one in order to place immediate implants in upper molar area.